Sweroside Alleviated LPS-Induced Inflammation via SIRT1 Mediating NF-κB and FOXO1 Signaling Pathways in RAW264.7 Cells - Rui Wang; Zhaoyue Dong; Xiaozhong Lan; Zhihua Liao; Min Chen (Molecules, 2019)
Pterocephalus hookeri was used as a traditional Chinese medicine for the treatment of rheumatoid arthritis. Sweroside was a main iridoid isolated from P. hookeri. The present study aimed to investigate the anti-inflammatory effect mechanism of sweroside. In RAW264.7 cells induced by lipopolysaccharide (LPS), the abnormal proliferation, the NO content increase, and the downregulated Sirtuin1 (SIRT1) expression were observed. Sweroside could alleviate the inflammation by inhibiting cell proliferation through arresting the cell cycle at the G0/G1 phase, by suppressing pro-inflammatory cytokines and by promoting anti-inflammatory cytokines in LPS-induced RAW264.7 cells. Further mechanism research indicated that sweroside could activate the SIRT1, then suppress the nuclear factor-kappa B (NF-κB) and promote the Forkhead transcription factor O1 (FOXO1) signaling pathways. The present study indicated that sweroside may be the main anti-inflammatory constituent of P. hookeri and a promising candidate for anti-inflammation therapy.